Gestational and neonatal outcomes of women with partial Dunnigan lipodystrophy - Valerio, Cynthia M.; Muniz, Raquel Beatriz Gonçalves; Viola, Luiz F.; Bartzen Pereira, Gabriela; Moreira, Rodrigo Oliveira; de Sousa Berriel, Marise Ribeiro; Montenegro Júnior, Renan Magalhães; Godoy-Matos, Amélio F.; Zajdenverg, Lenita (Frontiers in Endocrinology, 2024)
Introduction: Lipodystrophies are a group of disorders characterized by selective and variable loss of adipose tissue, which can result in an increased risk of insulin resistance and its associated complications. Women with lipodystrophy often have a high frequency of polycystic ovary syndrome (PCOS) and may experience gynecological and obstetric complications. The objective of this study was to describe the gestational outcomes of patients with familial partial lipodystrophy type 2 (FPLD2) at a reference center with the aim of improving the understanding and management of pregnant women affected by this condition. Methods: This was a retrospective analysis of data obtained from questionnaires regarding past pregnancies and a review of medical records from the beginning of follow-up in outpatient clinics. Results: All women diagnosed with FPLD2 who had previously become pregnant were included in this study (n=8). The women in the study experienced pregnancies between the ages of 14 and 38 years, with an average of 1.75 children per woman. The pregnancies in question were either the result of successful conception within 12 months of attempting to conceive or unplanned pregnancies. During pregnancy, two women (25%) were diagnosed with gestational diabetes mellitus (GDM), one (12.5%) with gestational hypothyroidism, and one (12.5%) with preeclampsia. Among the 17 pregnancies, four miscarriages (23.5%) occurred, and five cases (29.4%) of macrosomia were observed. Four instances of premature birth and an equal number of neonatal hypoglycemia cases were recorded. The reported neonatal complications included an unspecified malformation, respiratory infection, and two neonatal deaths related to heart malformation and respiratory distress syndrome. Conclusions: Our data showed a high frequency of fetal complications in women with FPLD2. However, no instances of infertility or prolonged attempts to conceive have been reported, highlighting the significance of employing effective contraception strategies to plan pregnancies at optimal times for managing metabolic comorbidities.